Human cytogenetics : constitutional analysis : a practical approach - Rooney, D. E (Oxford University Press, 2001)
Human Cytogenetics: Constitutional Analysis covers all basic aspects of human cytogenetic study other than malignancies and abnormalities. They are covered in a separate volume. Since the publication of the 2nd edition in 1992, there have been major advances in technology and the emphasis of this new edition is on the spectrum of technologies available to conventional and molecular cytogenetics. Perhaps the largest new development has been the transition of fluorescence in situ hybridization to an essential tool for all cytogenetecists and consequently its use in chromosome analysis is covered in detail. Another important new technology to be described in detail is computerised image analysis. The conventional techniques have not been forgotten, with chapters on chromosome staining and banding techniques and meiotic studies. New authors have been brought in to take a fresh look at lymphocyte culture and prenatal diagnosis. As before, there is an introduction to human chromosomes, their analyses, and the application of cytogenetic investigations to clinical practice. There is also an appendix on health and safety concerns in the cytogenetics laboratory. This book will be invaluable to any scientists using basic cytogenetics and along with its sister volume Human Cytogenetics: Malignancy and Acquired Abnormalities will be an essential purchase for any cytogenetics laboratory. The volumes are available individually or as a set.
Practical approach series
Keywords: cytogenetika; biologie; cytologie, klinická cytologie; Cytogenetics